Outcomes and prognostic variables associated with primary abdominal visceral soft tissue sarcomas in dogs: A Veterinary Society of Surgical Oncology retrospective study. (27th March 2019) - Linden, Dan; Liptak, Julius M.; Vinayak, Arathi; Grimes, Janet A.; Sandey, Maninder; Smiley, Whitney; Matz, Brad M.
Abstract : Primary abdominal visceral soft tissue sarcomas (STSs) are rare tumours in dogs with little information available on outcomes. The goal of this retrospective, multi‐institutional study was to describe the common tumour types, location and prognostic factors associated with primary abdominal visceral STSs. Medical records were searched for dogs with primary abdominal visceral STSs at six institutions and were retrospectively reviewed. Tumours were graded using the previously described grading scheme for STSs of the skin and subcutis when information in the histopathology report contained adequate details. Forty‐two dogs were included in the study. Five dogs had grade I tumours, 11 had grade II and 15 had grade III tumours. The most common tumour type was leiomyosarcoma (38.1%). The most common tumour locations were the spleen (47.6%) and small intestine (23.8%). The local recurrence rate was low (4.7%). Metastasis was present at the time of surgery in 23.8%, and the overall metastatic rate was 40.4%. Mitotic index of ≥9 was associated with significantly shorter survival time (MST 269 days) compared with a mitotic index of <9 (MST not reached). The MST for grade I STSs was not reached, was 589 days for grade II and 158 days for grade III. Dogs with grade III tumours were more likely to develop metastatic disease. Neither location of the primary tumour nor the histologic subtype was associated with survival time. Histologic grading of abdominal visceral STSs using the previously described scheme is prognostic and should be provided on histopathology reports.